Ultrasound enhanced the conjugation of epigallocatechin gallate on whey protein isolate and its influence on the emulsifying property and allergenicity - Chen, Lilan; Li, Haohui; Jiang, Chunyuan; Zuo, Baoer; Li, Meifeng; Li, Sining; Zhang, Xiaoning (Frontiers in Nutrition, 2025)
BackgroundThe conjugation of polyphenols to proteins provides a method for modifying the structure and properties of proteins.MethodsThis study investigated the roles of ultrasound in the conjugation of epigallocatechin gallate (EGCG) with whey protein isolate (WPI) and its effects on the structural characteristics and properties.Results and discussionThe formation of EGCG-WPI conjugates (EW) resulted in a decrease in free amino groups and thiol groups in WPI, accompanied by an increase in size and thermal stability. Consequently, this conjugation inhibited the immunoglobulin E (IgE) binding capacity and improved the emulsifying properties of WPI. Furthermore, ultrasound facilitated the interaction by producing larger size of conjugates (U-EW), increasing the binding affinity from 5.8 × 105 M−1 to 1.7 × 106 M−1 and the polyphenol bound equivalent from 80.4 ± 1.3 mg/g to 98.2 ± 1.9 mg/g compared to EW. It induced the greater changes in the secondary structure and surface hydrophobicity, thereby promoting greater participation of β-lactoglobulin (βLg) in conjugation with EGCG, and resulting in a higher inhibition rate of IgE binding capacity, an enhanced emulsifying property of U-EW. These findings will potentially expand the applications of WPI in the food industry.